The Students’ Perspectives on Extensive Listening Through YouTube - Suyik Binarkaheni; Titik Ismailia; Meiga Rahmanita (Politeknik Negeri Jember, 2022)
The paper reports a case study method exploring the perceptions of 10 students enrolling a listening class in terms of their experience when taking extensive listening, primarily by using YouTube. A closed-ended questionnaire was delivered and FGD through a semi-structured interview was utilized as a datacollecting method. The results of exploring the students’ perspectives indicated that: (1) they can do extensive listening via YouTube to improve their listening fluency anytime and anywhere; (2) they can learn the pronunciation of new vocabulary and grammar through extensive listening; (3) they can pertain the topic of aural text from context; (4) the speed change function and the subtitle function is occasionally used to solve their confusion on new phrases; (5) some commercials may be as information to support their English learning; (6) they find an unreliable or unstable internet connection in some cases. Therefore, it is suggested that teachers set the teaching and learning activities and environment that can encourage students to experience extensive listening. Besides, it is also suggested that the institution management provide good Internet accessibility in the teaching and learning environment.